(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Many elements on Earth occur in various atomic configurations called isotopes, which have identical atomic numbers but vary in atomic mass. Un-stable elements undergo disintegration through energy emission; isotopes that emit radiation are termed radioisotopes. The application of these isotopes in sectors including manufacturing, farming, medical services, and research institutions is presently of considerable significance. In the medical field, these isotopes are employed in nuclear medicine for diagnostic and therapeutic uses. Radionuclide imaging, or functional imaging, represents a medical specialty that uniquely enables the evaluation of physiological changes resulting from biochemical abnormalities, utilizing the radiotracer technique. Radioisotopes play a pivotal role in modern medicine, being widely used in diagnosis and therapy, contributing to improved disease detection accuracy and treatment effectiveness. In diagnostics, isotopes like technetium-99m (Tc) have been utilized in organ imaging via single-photon emission computed tomographic (SPECT), whereas fluorine-18 (F) was a crucial component in positron emission tomography (PET), facilitating the high-resolution identification of metabolic alterations within tissues. In therapy, isotopes like iodine-131 (I) were utilized to address thyroid diseases, while lutetium-177 (Lu) is an effective targeted therapy for some cancers. Despite the significant benefits of radioisotopes, challenges related to their availability, high cost, and radiation risks remain, necessitating the development of safer technologies and the production of isotopes using more efficient methods. The future of nuclear medicine depends on continued progress in targeted radiation therapy, improved imaging methods, and enhanced safety measures to ensure maximum therapeutic benefit with the least possible risks.